2D Simulation Of Sultan Abu Bakar Dam Release Using HEC-RAS - Faudzi, Siti Multazimah Mohamad (Universiti Sains Malaysia, 2017)
Dams are constructed as water storage to compensate for fluctuations in catchment area and to generate electricity. However, uncontrollable amount of discharges released from the gated spillways of the dam would impact the downstream area. On October 23 2013, floods occured in downstream of Sungai Bertam probably due to a huge volume of discharges were released from Sultan Abu Bakar (SAB) dam. Impacts of that flood, three people were confirmed dead and nearly 100 houses destroyed or under water while over 100 vehicles badly damaged. Thus, study on various maximum discharges released along 4 km and 200 m width downstream river was conducted. The main objectives in this study are to determine flood water level along 4 km width of Sungai Bertam based on SAB dam release. The flood water level can helps evaluate effect of in that area due to SAB dam release. The computer simulation was done to analyse various maximum discharges released from the gated spillway by using HEC-RAS which is constructed by US Army Corp. HEC-RAS software was used to aid in channel flow analysis and floodplain determination by researchers around the world. The amount of water release used in the simulation were 10, 25, 30, 50, 100, 230 and 300 m3/s. The water discharge were based on recommendation dam release by Tenaga Nasional Berhad (TNB). As a result, maximum depth, maximum velocity, arrival time and inundation boundary maps were produced. This finding will be able to produce flood hazard map and able to predict risk area of flooding. This study will also help authorities to control amount of maximum discharge level allowed from the dam as to prevent flood occur in downstream area of Sungai Bertam. Besides, this study can give awareness to local residents of risk area on flood wave travel time.